MARKETING STRATEGY FOR PROCESSED SMOKED FISH PRODUCTS ON THE MICRO, SMALL, AND MEDIUM SCALE POKLAHSAR IN TEGAL CITY - Aisah, Aisah; Mudzakir, Abdul Kohar; Noviyanti, Rinda (Fakultas Perikanan dan Ilmu Kelautan, Universitas Diponegoro, 2024)
Tegal City, located on the northern coast of Central Java, boasts abundant marine resources that support its thriving fisheries sector . However, the city faces various sustainable challenges in the processing of smoked fish by micro, small, and medium-scale Processing and Marketing Groups (Poklahsar), including obstacles in production, marketing, and product development. This research aims to formulate marketing strategies for smoked fish products processed by Poklahsar to increase sales. Using a qualitative and descriptive approach, this study involved 36 respondents from smoked fish processors. Data were collected through observation, interviews, and questionnaires to understand the socio-economic and technical conditions of Poklahsar. SWOT analysis was conducted to identify internal and external factors affecting marketing. The results indicate that the main strengths of the smoked fish business lie in the quality of raw materials, the availability of labor, and the market acceptance of the product's unique taste. However, weaknesses include limited packaging and marketing capabilities, as well as a lack of knowledge about information technology. Externally, there are opportunities to enter modern markets and utilize marketing technology, but challenges such as poor sanitation and intense competition pose threats. Based on the SWOT analysis, the business is positioned in quadrant 2, indicating that product diversification is the best approach to enhance competitiveness. Key recommendations include packaging innovation, capacity building for business actors, collaboration with the government, and strengthening distribution channels. Implementing these strategies is expected to increase sales and competitiveness of smoked fish products in Tegal City.